Los grabados históricos en las Peñas Chicas. La anexión de la Puna de Atacama desde una estancia de Antofagasta de la Sierra (Catamarca, Argentina) - Martinez, María Soledad (2020)
Research that addressed the annexation of the Atacama Puna by the Argentinian State in the early twentieth century has focused inquiry on the documentary archive produced by travelers, expeditions, and the administrative bureaucracy. This research was central to the characterization of the social processes and state impact over a territory conceived of as marginal and located in the confines-both geographical and subjective-of the nation. Taking the analysis of rock art engravings located in an estancia in Antofagasta de la Sierra, Catamarca, as a starting point, this paper instead approaches the annexation of the Puna from the material evidence. From an archaeological point of view, and from the rock art representations in particular, we suggest that markings inscribed in the ignimbrite walls and associated with the estancia, provide evidence of the new political and administrative situation in which the families from the Puna developed their social present more than a century ago.